Method for preparing silicon-carbon composite material, negative pole piece and secondary battery
The preparation of nanoporous silicon-carbon composite materials by one-step method solves the problems of energy density and cycling performance of traditional negative electrode materials, and achieves the improvement of electrochemical performance of secondary batteries with high discharge capacity and good cycling stability.
Patent Information
- Application Number
- CN202411436488.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-18
AI Technical Summary
The theoretical specific capacity of traditional graphite-based anode materials has approached the limit, making it difficult to increase the energy density of lithium-ion batteries. In addition, the volume expansion of the silicon-based anode materials during charging and discharging leads to structural damage, limiting their application.
A one-step method is used to prepare nanoporous silicon-carbon composite materials. By performing reduction reactions and carbonization coating reactions in an inert atmosphere, the process flow is simplified, the reaction time and energy consumption are shortened, and a carbon-coated silicon-carbon composite material is prepared.
It improves the discharge capacity and cycle stability of secondary batteries, reduces the cost and process complexity of silicon material preparation, and promotes the industrial mass production of silicon-carbon composite materials.
Smart Images

Figure CN119481023A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a method for preparing a silicon-carbon composite material, a negative electrode sheet and a secondary battery. Background Art
[0002] With the growing demand for clean energy, lithium-ion batteries and sodium-ion batteries have become research hotspots due to their high energy density and long life. However, traditional graphite-based negative electrode materials have the problem of low theoretical specific capacity, which limits the improvement of the overall performance of the battery. The energy density of lithium-ion batteries has become an urgent problem to be solved. Graphite, a widely used negative electrode material for lithium-ion batteries, has an actual specific capacity close to the theoretical specific capacity limit of 372mAh / g. It is difficult to make a big breakthrough in capacity improvement, so it is difficult to meet the greater energy density of power batteries. Therefore, it is urgent to develop a new generation of high energy density negative electrode materials.
[0003] Silicon-based negative electrode materials have extremely high specific capacity (theoretically up to 4200mAh / g) and suitable lithium insertion potential, and are considered to be the most promising negative electrode materials to replace carbon materials. However, the volume expansion of silicon negative electrode materials during the charging and discharging process of lithium-ion batteries is more than 300%, which will destroy the structure of the silicon material and cause the material to pulverize, resulting in large irreversible capacity loss and poor cycle performance of the silicon-based negative electrode, limiting its application in lithium-ion batteries. Therefore, research on silicon-based negative electrode materials needs to be further deepened. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to provide a method for preparing a silicon-carbon composite material, wherein the silicon-carbon composite material prepared by the method is applied to a secondary battery and has a high discharge capacity and good cycle stability.
[0005] In one aspect of the present invention, the present invention provides a method for preparing a silicon-carbon composite material. According to an embodiment of the present invention, the method for preparing a silicon-carbon composite material comprises: uniformly mixing a silicon oxide silicon source, a reducing agent, a molten salt and a carbon source precursor to obtain a mixed raw material; in an inert atmosphere, allowing the mixed raw material to undergo a reduction reaction and a carbonization coating reaction at a predetermined temperature to obtain a pre-product mixture; washing the pre-product mixture to obtain the silicon-carbon composite material of carbon-coated silicon. Thus, a one-step method is adopted to prepare a nanoporous silicon-carbon composite material. During the preparation process, while the reducing agent reduces silicon oxide to obtain a silicon material, the carbon source precursor is carbonized to obtain a carbon material, and the carbon material carbon-coates the silicon material. The above three reaction processes are carried out simultaneously, which greatly simplifies the reaction process and further shortens the process reaction time and energy consumption; the prepared silicon-carbon composite material is used as the negative electrode of a secondary battery, and the electrochemical performance of the battery is significantly improved, with a high discharge capacity and good cycle stability.
[0006] According to an embodiment of the present invention, the reduction reaction and the carbonization coating reaction are carried out in a reaction kettle.
[0007] According to an embodiment of the present invention, the silicon oxide silicon source includes at least one of diatomaceous earth, high-silicon zeolite, rice husk, silicon oxide particles, silicon oxide aerogel and silicate glass powder.
[0008] According to an embodiment of the present invention, the molten salt includes anhydrous aluminum chloride, anhydrous magnesium chloride and / or anhydrous zinc chloride; and / or the reducing agent includes magnesium powder and / or aluminum powder; and / or the carbon source precursor includes glucose, sucrose, starch, citric acid, asphalt, chitosan, petroleum coke, kerosene coke, phenolic resin, graphene and biomass carbon.
[0009] According to an embodiment of the present invention, the mass ratio of the silicon oxide silicon source, the reducing agent, the molten salt and the carbon source precursor is 1:(1-8):10:(0.5-3).
[0010] According to an embodiment of the present invention, the predetermined temperature is 200° C. to 600° C., and / or the time for the reduction reaction and the carbonization coating reaction to occur is 1 to 12 hours.
[0011] According to an embodiment of the present invention, the reducing agent is magnesium powder, and the predetermined temperature is 200°C to 400°C; the reducing agent is aluminum powder, and the predetermined temperature is 200°C to 600°C.
[0012] According to an embodiment of the present invention, the cleaning is acid cleaning, and the acid cleaning comprises: first cleaning the pre-product mixture in hydrochloric acid, and then performing a second cleaning with hydrofluoric acid to obtain the silicon-carbon composite material.
[0013] In another aspect of the present invention, the present invention provides a negative electrode plate. According to an embodiment of the present invention, the negative electrode plate includes a silicon-carbon composite material prepared by the method described above. As a result, the electrochemical performance of the negative electrode plate is better, which helps to improve the discharge capacity and cycle stability of the secondary battery. It can be understood by those skilled in the art that the negative electrode plate has all the characteristics and advantages of the silicon-carbon composite material described above, and no more details are given here.
[0014] In another aspect of the present invention, the present invention provides a secondary battery. According to an embodiment of the present invention, the secondary battery comprises the above-mentioned negative electrode sheet. The secondary battery of the present invention has a high discharge capacity and good cycle stability.
[0015] The technical solution of the present invention has at least the following technical effects:
[0016] First, the present invention adopts a one-step method to prepare a nanoporous silicon-carbon composite material. During the preparation process, while the reducing agent reduces silicon oxide to obtain a silicon material, the carbon source precursor is carbonized to obtain a carbon material, and the carbon material carbon-coates the silicon material. The above three reaction processes are carried out simultaneously, which greatly simplifies the reaction process and further shortens the process reaction time and energy consumption.
[0017] Second, by using diatomaceous earth, rice husk and other abundant and low-priced silicon oxide as silicon source, it is beneficial to control the cost of silicon source materials and reduce the production cost of the entire process;
[0018] Thirdly, the silicon-carbon composite material prepared by the method of the present invention has a high discharge capacity and good cycle stability when applied to a secondary battery;
[0019] Fourth, the above preparation method can solve the problems of complex preparation conditions, high cost, and complex process of silicon materials, and is conducive to the industrial mass production of silicon-carbon composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0021] Figure 1 It is a flow chart of a method for preparing a silicon-carbon composite material in one embodiment of the present invention. DETAILED DESCRIPTION
[0022] Below will be explained with reference to embodiment of the present invention.It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention.In the embodiment, if no specific technology or condition is indicated, it is carried out according to the technology or condition described in the document in this area or according to the product specification.The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be purchased from the market.
[0023] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0024] In one aspect of the present invention, the present invention provides a method for preparing a silicon-carbon composite material. According to an embodiment of the present invention, the method for preparing a silicon-carbon composite material comprises:
[0025] S100: uniformly mixing a silicon oxide silicon source, a reducing agent, a molten salt and a carbon source precursor to obtain a mixed raw material.
[0026] According to some embodiments of the present invention, the silicon oxide silicon source includes at least one of diatomite, high-silicon zeolite, rice husk, silicon oxide particles, silicon oxide aerogel and silicate glass powder. Therefore, by using diatomite, high-silicon zeolite, rice husk and other abundant and low-priced silicon oxide as the silicon source, it is beneficial to control the cost of silicon source materials and reduce the production cost of the entire process; at the same time, it can ensure a good yield of preparing silicon-carbon composite materials.
[0027] According to some embodiments of the present invention, the molten salt includes anhydrous aluminum chloride, anhydrous magnesium chloride and / or anhydrous zinc chloride. The molten salt is melted at a predetermined temperature in the subsequent step S200, and particles or powders of silicon oxide silicon source, reducing agent, etc. are evenly dispersed in the molten salt, which is conducive to the smooth progress of reduction, carbonization, coating and other reactions.
[0028] According to some embodiments of the present invention, the reducing agent includes magnesium powder and / or aluminum powder. The above-mentioned reducing agent can reduce the silicon oxide silicon source to silicon at a relatively low temperature (200-600°C). When magnesium powder is used as a reducing agent, the rate of the reduction reaction can be increased, and the reduction reaction can be successfully completed at a relatively low temperature of 200-400°C; when aluminum powder is used as a reducing agent, the silicon oxide reduction temperature is lowered while using aluminum powder with slightly lower activity to reduce safety risks during the reaction, while reducing reaction energy consumption and reducing electricity costs.
[0029] According to some embodiments of the present invention, the carbon source precursor includes glucose, sucrose, starch, citric acid, asphalt, chitosan, petroleum coke, kerosene coke, phenolic resin, graphene and biomass carbon. The above carbon sources are widely available, easy to prepare or purchase, and have low cost and are easy to carbonize.
[0030] According to some embodiments of the present invention, the reduction reaction and the carbonization coating reaction are carried out in a reactor, that is, the subsequent step S200 is carried out in a reactor, so that before the reaction, a mixed raw material such as a silicon oxide silicon source, a reducing agent, a molten salt and a carbon source precursor is placed in the reactor under an inert atmosphere. In this way, during the reaction process, the sealed reactor is in a certain high-pressure environment, and under an inert atmosphere and high-pressure environment, the carbonization temperature of the carbon source can be further reduced (for example, the carbonization temperature under conventional normal pressure is about 1000°C).
[0031] According to an embodiment of the present invention, the mass ratio of silicon oxide silicon source, reducing agent, molten salt and carbon source precursor is 1: (1-8): 10: (0.5-3), such as the mass ratio of 1: 1: 10: 0.5, 1: 2: 10: 1, 1: 3: 10: 1.5, 1: 4: 10: 2, 1: 5: 10: 2.5, 1: 6: 10: 3, 1: 7: 10: 2, 1: 8: 10: 2, etc. When the mixed raw materials react under the above ratio, the sufficiency of the reaction of each raw material can be fully guaranteed, and the utilization rate of the raw materials can be improved.
[0032] S200: In an inert atmosphere, the mixed raw materials are subjected to a reduction reaction and a carbonization coating reaction at a predetermined temperature to obtain a pre-product mixture.
[0033] In some specific embodiments, the mixed raw material is placed in a reactor in an inert gas atmosphere, and a predetermined temperature of the reaction is set (for example, the reactor is placed in a muffle furnace set at a predetermined temperature), so that the mixed raw material undergoes reduction, carbonization, and coating reactions at the predetermined temperature. Thus, the high-pressure inert gas in the reactor is used to reduce the carbonization conditions of the carbon source material, so that the carbonization temperature of the carbon source precursor is reduced, energy consumption and pollution are reduced, and production costs are reduced.
[0034] According to an embodiment of the present invention, the predetermined temperature is 200°C to 600°C, and the time for the reduction reaction and the carbonization coating reaction to occur is 1 to 12 hours, such as 4 to 10 hours. It can be seen that the temperature for reducing silicon oxide and coating silicon materials is low, the energy consumption is low, the environmental pollution is reduced, and the production cost can be reduced, which plays a positive role in the large-scale commercial application of silicon materials.
[0035] In some specific embodiments, the reducing agent is magnesium powder, which has a relatively high reaction activity and can increase the rate of the reduction reaction. The reduction reaction can be successfully completed at a relatively low temperature of 200-400°C; when aluminum powder is used as the reducing agent, the predetermined temperature is 200°C-600°C. While lowering the silicon oxide reduction temperature, using aluminum powder with slightly lower activity reduces safety risks during the reaction, while reducing reaction energy consumption and reducing electricity costs.
[0036] In some embodiments of the present invention, the reaction temperature (ie, the predetermined temperature) in the reactor can be gradually increased to the desired reaction temperature at a certain rate, such as increasing the temperature at 4-8° C. / min.
[0037] Furthermore, the inert gas includes but is not limited to nitrogen, argon and other gases.
[0038] S300: washing the pre-product mixture to obtain a silicon-carbon composite material of carbon-coated silicon.
[0039] According to an embodiment of the present invention, the cleaning is pickling, and the pickling includes: firstly cleaning the pre-product mixture in hydrochloric acid, and then performing a second cleaning with hydrofluoric acid to obtain the silicon-carbon composite material. By pickling, impurities such as metal oxides and metals in the pre-product mixture can be effectively removed.
[0040] Furthermore, in some specific embodiments, the pickling step includes: first cleaning the pre-product mixture in 0.5-1 mol / L hydrochloric acid for 2-10 h, and then performing a second cleaning with 0.5 mol / L hydrofluoric acid for 0.5-2 h to obtain a relatively pure silicon-carbon composite material.
[0041] According to an embodiment of the present invention, a one-step method is adopted to prepare a nanoporous silicon-carbon composite material. During the preparation process, while a reducing agent reduces silicon oxide to obtain a silicon material, a carbon source precursor is carbonized to obtain a carbon material, and the carbon material carbon-coates the silicon material. The above three reaction processes are carried out simultaneously, which optimizes the process steps, greatly simplifies the reaction process, and further shortens the process reaction time and energy consumption. The prepared silicon-carbon composite material is used as the negative electrode of a secondary battery, and the electrochemical performance of the battery is significantly improved, and it has a higher discharge capacity and good cycle stability.
[0042] In another aspect of the present invention, the present invention provides a negative electrode plate. According to an embodiment of the present invention, the negative electrode plate includes a silicon-carbon composite material prepared by the method described above. As a result, the electrochemical performance of the negative electrode plate is better, which helps to improve the discharge capacity and cycle stability of the secondary battery. It can be understood by those skilled in the art that the negative electrode plate has all the characteristics and advantages of the silicon-carbon composite material described above, and no more details are given here.
[0043] In some embodiments, in addition to the above-mentioned silicon-carbon composite material as an active material, the negative electrode plate may further include components such as a conductive agent, a binder and a solvent. The raw materials are mixed in the required proportions to obtain a negative electrode slurry of suitable viscosity, and the negative electrode slurry is coated on the surface of the current collector. After curing and drying, the negative electrode plate is obtained.
[0044] In another aspect of the present invention, the present invention provides a secondary battery. According to an embodiment of the present invention, the secondary battery comprises the above-mentioned negative electrode sheet. The secondary battery of the present invention has a high discharge capacity and good cycle stability.
[0045] According to an embodiment of the present invention, the secondary battery may be a storage battery such as a lithium ion battery or a sodium ion battery.
[0046] Those skilled in the art can understand that, in addition to the above-mentioned negative electrode plate, the secondary battery also includes a positive electrode plate, a separator, an electrolyte, a shell and other structures.
[0047] According to an embodiment of the present invention, the secondary battery can be used in electrical devices such as vehicles, mobile phones, tablets, robots, etc.
[0048] Example
[0049] Example 1
[0050] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0051] (1) grinding diatomaceous earth, aluminum powder and sucrose in a mass ratio of 1:1:0.5, mixing them evenly to obtain a first mixture;
[0052] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed in a mass ratio of 4:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0053] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 200° C. at a heating rate of 5° C. / min, and kept at this temperature for 12 hours to obtain a pre-product mixture.
[0054] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 6 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0055] Example 2
[0056] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0057] (1) grinding diatomaceous earth, aluminum powder and sucrose in a mass ratio of 1:4:0.5, mixing them evenly to obtain a first mixture;
[0058] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed at a mass ratio of 1.8:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0059] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 200° C. at a heating rate of 5° C. / min, and kept at this temperature for 12 hours to obtain a pre-product mixture.
[0060] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0061] Example 3
[0062] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0063] (1) putting diatomaceous earth, aluminum powder and sucrose into a grinder in a mass ratio of 1:1:2, grinding and mixing evenly to obtain a first mixture;
[0064] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed at a mass ratio of 2.5:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0065] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 200° C. at a heating rate of 5° C. / min, and kept at this temperature for 12 hours to obtain a pre-product mixture.
[0066] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0067] Example 4
[0068] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0069] (1) grinding diatomaceous earth, aluminum powder and asphalt in a mass ratio of 1:1:0.5, mixing them evenly to obtain a first mixture;
[0070] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed in a mass ratio of 4:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0071] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 600° C. at a heating rate of 5° C. / min, and kept at this temperature for 2 hours to obtain a pre-product mixture.
[0072] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0073] Example 5
[0074] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0075] (1) grinding diatomaceous earth, magnesium powder and sucrose in a mass ratio of 1:1:0.5, mixing them evenly to obtain a first mixture;
[0076] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed in a mass ratio of 4:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0077] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 200° C. at a heating rate of 5° C. / min, and kept at this temperature for 12 hours to obtain a pre-product mixture.
[0078] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0079] Example 6
[0080] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0081] (1) putting rice husk, magnesium powder and sucrose into a mill in a mass ratio of 1:1:0.5, grinding and mixing evenly to obtain a first mixture;
[0082] (2) placing the first mixture and the autoclave into a glove box filled with an inert gas of nitrogen, mixing anhydrous magnesium chloride and the first mixture in a mass ratio of 4:1, and mixing them evenly to obtain a second mixture (i.e., the mixed raw material).
[0083] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 200° C. at a heating rate of 5° C. / min, and kept at this temperature for 12 hours to obtain a pre-product mixture.
[0084] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0085] Example 7
[0086] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0087] (1) grinding rice husks, magnesium powder and sucrose in a mass ratio of 1:1:0.5, mixing them evenly to obtain a first mixture;
[0088] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed in a mass ratio of 4:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0089] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 400° C. at a heating rate of 5° C. / min, and kept at this temperature for 12 hours to obtain a pre-product mixture.
[0090] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0091] Example 8
[0092] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0093] (1) grinding diatomaceous earth, magnesium powder and sucrose in a mass ratio of 1:1:0.5, mixing them evenly to obtain a first mixture;
[0094] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed in a mass ratio of 4:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0095] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 400° C. at a heating rate of 5° C. / min, and kept at this temperature for 4 hours to obtain a pre-product mixture.
[0096] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0097] Comparative Example 1
[0098] A specific method for preparing a silicon-carbon composite material comprises the following steps:
[0099] (1) grinding diatomaceous earth and aluminum powder in a mass ratio of 1:1 and mixing them uniformly to obtain a first mixture;
[0100] (2) The first mixture and the autoclave are placed in a glove box filled with an inert gas of nitrogen, and anhydrous aluminum chloride and the first mixture are mixed in a mass ratio of 5:1, and the second mixture (i.e., the mixed raw material) is obtained after mixing evenly.
[0101] (3) The second mixture is loaded into a high-pressure reactor, and the high-pressure reactor is placed in a muffle furnace, and the temperature is increased to 200° C. at a heating rate of 5° C. / min, and kept at this temperature for 12 hours to obtain a pre-product mixture.
[0102] (4) The pre-product mixture is acid-washed with 1 mol / L hydrochloric acid for 2 h, and then acid-washed with 0.5 mol / L hydrofluoric acid for 0.5 h, and then filtered and dried to obtain a silicon-carbon composite material.
[0103] Comparative Example 2
[0104] (1) 10 g of silicon oxide was washed three times with 50 ml of deionized water and then transferred to a 100° C. oven and dried for 7 days to obtain a completely dehydrated raw material;
[0105] (2) placing silicon oxide in a 350° C. tube furnace and pre-calcining for 3 h in a nitrogen atmosphere to obtain a silicon oxide pre-calcined sample;
[0106] (3) grinding the silicon oxide pre-calcined sample and glucose together and putting them into the tube furnace again, and calcining them at 900 °C for 4 h under nitrogen atmosphere to obtain a Si@C crude sample;
[0107] (4) The Si@C crude sample was acid-washed once in a hydrochloric acid solution, washed three times in deionized water, and then placed in a 100°C oven for high-temperature drying for 7 days to obtain a Si@C composite material, i.e., a silicon-carbon composite material.
[0108] Under the same conditions, the silicon-carbon composite materials prepared in all the above embodiments and comparative examples were used to prepare negative electrode sheets, and then the negative electrode sheets were assembled into button lithium-ion batteries to obtain 2032 button batteries. The button batteries were subjected to 1C charge and discharge tests to obtain electrochemical properties such as the first efficiency and cycle performance of each battery. The results are shown in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] By comparing Examples 1 to 8 with Comparative Example 1, it can be seen that preparing the negative electrode plate by using the carbon-coated silicon composite material is helpful to improve the first efficiency and cycle retention rate of the battery, that is, to improve the cycle stability of the battery. It also shows that the silicon-carbon composite material prepared by the above method in the present invention can be used as a negative electrode material for the battery to improve the discharge capacity and cycle stability of the battery.
[0113] By comparing Examples 1 to 8 with Comparative Example 2, it can be seen that during the preparation process, the entire process time of the embodiments of the present invention is shorter and the reaction temperature is lower (lower than 600°C), while the reaction temperature in Comparative Example 2 is as high as 900°C. It can also be seen from the test data in Table 1 that, compared with Comparative Example 2, the silicon-carbon composite material prepared by the above method in the present invention as a battery negative electrode material can better improve the discharge capacity and cycle stability of the battery.
[0114] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0115] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0116] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: include: The silicon oxide silicon source, the reducing agent, the molten salt and the carbon source precursor are uniformly mixed to obtain a mixed raw material; In an inert atmosphere, causing the mixed raw materials to undergo a reduction reaction and a carbonization coating reaction at a predetermined temperature to obtain a pre-product mixture; The pre-product mixture is washed to obtain the silicon-carbon composite material of carbon-coated silicon.
2. The method according to claim 1, characterized in that The reduction reaction and the carbonization coating reaction are carried out in a reaction kettle.
3. The method according to claim 1, characterized in that The silicon oxide silicon source comprises at least one of diatomaceous earth, high-silicon zeolite, rice husk, silicon oxide particles, silicon oxide aerogel and silicate glass powder.
4. The method according to claim 1, characterized in that The molten salt includes anhydrous aluminum chloride, anhydrous magnesium chloride and / or anhydrous zinc chloride; And / or, the reducing agent includes magnesium powder and / or aluminum powder; And / or, the carbon source precursor includes glucose, sucrose, starch, citric acid, asphalt, chitosan, petroleum coke, kerosene coke, phenolic resin, graphene and biomass carbon.
5. The method according to claim 1, characterized in that The mass ratio of the silicon oxide silicon source, the reducing agent, the molten salt and the carbon source precursor is 1:(1-8):10:(0.5-3).
6. The method according to claim 3, characterized in that The predetermined temperature is 200° C. to 600° C., and / or the time for the reduction reaction and the carbonization coating reaction to occur is 1 to 12 hours.
7. The method according to claim 1, characterized in that The reducing agent is magnesium powder, and the predetermined temperature is 200°C to 400°C; the reducing agent is aluminum powder, and the predetermined temperature is 200°C to 600°C.
8. The method according to claim 1, characterized in that The cleaning is acid cleaning, and the acid cleaning comprises: first cleaning the pre-product mixture in hydrochloric acid, and then performing a second cleaning with hydrofluoric acid to obtain the silicon-carbon composite material.
9. A negative electrode plate, characterized in that: A silicon-carbon composite material prepared by the method according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 9.
